Estimating the Economic Benefits of Eliminating Job Strain as a Risk Factor for Depression. Issue 1 (January 2017) - Cocker, Fiona; Sanderson, Kristy; LaMontagne, Anthony D.
Abstract : Objective: The aim of this study was to quantify the economic benefits of eliminating job strain as a risk factor for depression, using published population-attributable risk estimates of depression attributable to job strain (13.2% for men, 17.2% for women). Methods: Cohort simulation using state-transition Markov modeling estimated costs and health outcomes for employed persons who met criteria for lifetime DSM-IV major depression. A societal perspective over 1-year and lifetime time horizons was used. Results: Among employed Australians, 890 million (5.8%) of the annual societal cost of depression was attributable to job strain. Employers bore the brunt of these costs, as they arose from lost productive time and increased risk of job turnover among employees experiencing depression. Conclusions: Proven, practicable means exist to reduce job strain. The findings demonstrate likely financial benefits to employers for expanding psychosocial risk management, providing a financial incentive to complement and reinforce legal and ethical directives. Abstract : Supplemental Digital Content is available in the text